National Service for Health : the Labour Party's post-war policy (London : Labour Party)
1943-04 1943 1940s 24 pages (2) For this reorganisation, the nation will need all, and more than all, the efficient hospitals that there are at present — both public and "voluntary." All those that come up to standard and can be fitted into the scheme should be brought within a coherent plan — a plan that is reasonably elastic and constantly brought up to date. This means that voluntary, as well as public hospitals, must be brought into the National Scheme, on terms which will satisfy the nation's sense of equity. The Labour Party therefore proposes that the Government should lay upon Local Authorities the duty of securing a comprehensive hospital service, based on a coherent but adaptable plan, each plan covering a large area — a "Region." All hospitals within the area, whether public or voluntary, general or special, should be required to come into and conform to this plan, undertaking only the type of work which is allotted to them in the plan. The standard of efficiency, and the conditions of service and staff should become the same for all, and all should be subject to inspection by inspectors responsible to the Ministry of Health. The voluntary hospitals should be required to admit all patients in accordance with a unified system of admission covering the whole hospital service. A simple method of achieving the goal of a unified hospital system would be as follows. The voluntary hospitals might receive financial assistance in respect of the cases referred to them by Local Authorities, and the Local Authorities would become entitled to a share of representation and control on the Governing Board of the hospital which is proportionate to the services rendered to the patients thus referred. The effect of this scheme would be to ensure that before long the voluntary hospitals will come under the control of the Local Authorities, and that the conditions of service and staff in all the hospitals will become standardised. Thus we should have at last a unified hospital system, laid out on a rational plan, each section of the plan covering a sufficiently large area for efficient working. (3) The staffing of Divisional Hospitals should be of the highest possible standard. A hospital of the size indicated would need a staff of about 50 doctors of various types. Specialists would see cases referred to them at the hospital, and should also be available for consultations at the Health Centres or in the patients' homes. The specialists' service should be so organised by the Divisional Hospital and the Divisional Health Centre in co-operation as to be available at short notice at all times. It is important that the doctors working in the Home Doctor Service should be able to keep in close touch not only with the cases which they have themselves sent to the hospital, but also with the hospital's general work. Divisional Health Centres The Government should require Local Authorities to establish Divisional and Local Health Centres as soon as conditions permit, and should offer grants for this purpose, sufficient to cover a large proportion of the cost. Each Divisional Centre should, where practicable, be close to a Divisional Hospital. Its equipment should provide for the widest possible range of services, including those that cannot always be provided at Local Centres. There should be a laboratory adequate for the service of the Divisional Hospital and Health Centre, and it should be staffed and equipped on a scale sufficient to allow for research. The clinical pathologist in charge of a laboratory should co-operate with the whole staff of the division, including the doctors in general practice, so as to facilitate research work throughout the area. 16 36/H24/40